P 127 Vigilance regulation in adult ADHD. Issue 10 (October 2017) - Strauß, M.; Paucke, M.; Sander, C.; Hegerl, U.
Abstract : Background: Functional regulation of vigilance or wakefulness is crucial for interaction with the environment and can be described as a unique, situation-dependent characteristic. Disorders of wakefulness regulation manifest themselves as delayed or rash declines in vigilance under calm settings. The vigilance model of affective disorders and ADHS postulate that unstable regulation of vigilance ("CNS arousal") is observed not only in overtired children, but also in patients with mania and ADHS. Moreover, sensation and novelty seeking, hyperactivity and impulsivity observed in such persons should be interpreted as an autoregulatory attempt to stabilise vigilance by creating a stimulus incentive environment. As in mania, also in ADHD several EEG-based studies indicate an unstable regulation of wakefulness. Using an EEG-based algorithm (Vigilance Algorithm Leipzig, VIGALL) to assess the transition from high wakefulness to drowsiness until sleep onset, paediatric ADHD as well as manic patients showed an unstable vigilance regulation with rapid declines to lower vigilance stages or sleep onset. We investigated whether the vigilance regulation in adult patients with ADHD is less stable than that of healthy controls by exploring the frequency of EEG-vigilance regulation patterns. Methods: Resting EEG recordings of unmedicated adult ADHD patients and healthy controls were analysed. The diagnosis was provided based on the DSM-IV criteria. EEG recordings of 15 min under quiet rest with eyes closed were performed. The computer-based Vigilance Algorithm Leipzig (VIGALL) was used to classify 1-s EEG segments into stages on the continuum ranging from full wakefulness to sleep onset. Results/conclusions: Patients with ADHD showed an unstable vigilance regulation and spent more time in the less vigilance stages compared to the healthy controls. The investigated vigilance regulation model in ADHD could establish new insights into the neurophysiology of ADHD in adulthood and should be the subject of further investigations. An additional pre-post-treatment investigation with view on the suitability of the vigilance regulation as a predictor for response after a treatment with psychostimulants appears also useful.